Investigations and fabrication of Ni(OH)2 encapsulated carbon nanotubes nanocomposites based asymmetrical hybrid electrochemical supercapacitor. (December 2020) - Ranjithkumar, R.; Arasi, S. Ezhil; Devendran, P.; Nallamuthu, N.; Lakshmanan, P.; Sudhahar, S.; Arivarasan, A.; Kumar, M. Krishna
Highlights: Ni(OH)2 /CNT nanocomposite was synthesised by chemical reflux method. Ni(OH)2 /CNT nanocomposite has peak specific capacitance about 876.5 Fg −1 . Nanocomposite exhibits 95% cyclic retention for 5000 cycles. Asymmetrical supercapacitor with Ni(OH)2 /CNT was fabricated. Asymmetrical supercapacitor exhibits high specific power about 12000 W/Kg. Abstract: The optimized electronic and ionic conductivity to minimize the total resistance in electrodes are investigated for the nickel hydroxide-carbon nanotubes nanocomposites synthesised by the chemical reflux method. The powder X-ray diffraction results revealed that, Ni(OH)2 nanoparticles successfully encapsulated with carbon nanotubes and title composite was formed. The existence of important vibrations of CNT and Ni(OH)2 was confirmed by FTIR spectra. Surface microstructure patterns were recorded by scanning electron microscopy (SEM) in different parts of the sample with different magnification. The SEM analysis revealed that, Ni(OH)2 mixed well with carbon nanotubes. Energy dispersive X-ray analysis confirmed the existence of elements present in the synthesised composite and with good agreement between experimental and theoretically values. The electrode was prepared from the synthesised Ni(OH)2 /CNT nanocomposite and specific capacitance measurement was made to it by using potentiostat. Charge-discharge ability of Ni(OH)2 /CNT electrode was analysed and its results are presented. Electrochemical oxidation-reduction behaviour of Ni-CNT composite was investigated by cyclic voltametery. The electrochemical impedance spectra revealed that, internal resistance between electrode/electrolyte interface play significant role and results are presented. Graphical absrtact: Image, graphical abstract